A secure online examination system - Dasarathan, Monisha (Nanyang Technological University, 2022)
The COVID-19 pandemic has made a huge lifestyle shift to all aspects of society – especially in educational institutions. In most educational institutions, examinations have long been the most efficient form of allowing students to revise the information learnt throughout the educational term. To ensure that examinations are fair, they are usually held in physical examination halls under the watchful eyes of invigilators who will ensure an even playing ground amongst all students. However, due to the pandemic, examinations had to be moved onto a remote platform online. Hence, it has become a crucial need to create a secure online examination system where students can be monitored by invigilators in real-time so as to ensure a fair examination. To achieve this objective, this project will be creating an online examination system where the system will be split into 3 user roles – course administrators, students and invigilators. My project will be fulfilling the tasks from the administrator’s point of view. An administrator’s role is to maintain examination records such as details of the examination, exam papers, student name lists etcetera. The secondary function of administrators would be to assist students and invigilators during an examination. In this project, administrator will be managing an automated chat bot that answers queries of students and invigilators. For the convenience of future development, this system is built using popular Python framework - Flask while using a XAMPP database server. We have accomplished to develop a secure online examination system that is capable of allowing multiple students to sit for an examination within the recesses of their house. Invigilators will also be able to monitor these students from a remote location. The administrator’s portion of the system will be laying the system groundwork for the students who have to take the exam, and also for the invigilator who will be proctoring the examination.